'Do nurses really do that'? An exploratory mixed methods study of Students' willingness to lead. (May 2021) - Topola, Leanne; Miller, Kathleen
Abstract: Background: Health care needs are changing, requiring nurses to assume leadership roles and engage in political activism to impact health system transformation. Nursing education socializes students to the profession, as this is where they begin to develop their professional identity. For these reasons' educators must begin to explore student perceptions of the role of the registered nurse given the emphasis on leadership and health care transformation and question if students want to assume these roles. Objectives: To identify first- and fourth-year baccalaureate nursing student perceptions of the role of the nurse and analyze their willingness to participate in roles that embody leadership and political action. Design: An exploratory mixed method design. Setting: Two western Canadian four-year baccalaureate nursing programs. Participants: First- and fourth-year students. Methods: This study utilized a survey to collect demographic data and broad student perceptions of the registered nurse role and career aspirations. Focus groups followed with a sub-set of participants to further explore student opinions about the role of nurses. Results: Similar perceptions and views of nursing exist among cohorts (first- and fourth-year students) and between Baccalaureate programs. Students continue to choose nursing as a career for altruistic reasons. Validation of their role is in the form of personal affirmation of a job well done from their patients. While there is acknowledgement among first- and fourth- year students that nurses should be leaders and influence the overall health care system, student responses indicated that the 'other guy' should do it, not them. Conclusions: The results identify the need to develop and implement strategies to prepare future nurses who are interested and willing to participate in a career based on leadership, political action, and healthcare transformation.